Tomato cultivation in a protected environment under different soil water tensions (Research, Society and Development, 2020)
Different tomato cultivars may have different water requirements, making it essential to study water demand. Thus, the objective was to evaluate the influence of different water tensions in the soil on the production and postharvest quality of tomato fruits, cultivar Dominador F1, under protected cultivation and drip irrigated. The experiment was installed in a greenhouse with a randomized block design, with four replications. The treatments consisted of six water tensions in the soil as indicative of the time to irrigate. The pre-established stresses were 20, 45, 70, 95, 120 and 145 kPa at a depth of 20 cm. At 140 days after transplanting, the variables evaluated were: total, commercial and non-commercial fruit production; total, commercial and non-commercial fruit productivity; number of fruits per plant; classification of commercial fruits; average mass of commercial fruits; incidence of apical rot (%); water use efficiency (USA); titratable acidity (AT); total soluble solids (TSS); pH; ratio of total soluble solids and titratable acidity (SST / AT); soluble pectin; vitamin C; firmness; color and macro and micronutrient content of the aerial part. The results showed that to obtain the highest values ​​of production and productivity of commercial fruits, number of fruits per plant, number of large and medium fruits and average mass of commercial fruits, one must irrigate when the water tension in the soil is, around 20 kPa, at a depth of 0.20 m. The different water tensions in the soil did not significantly influence the titratable acidity, pH, ratio of total soluble solids and titratable acidity and soluble pectin. The efficiency in the use of water, due to the water tensions in the soil, increased up to the tension of 116.57 kPa. From the quality characteristics evaluated, the levels of total soluble solids, vitamin C, firmness and color L * index, showed a significant effect with the water stresses in the soil.